RNase activity in erythroid cell lysates - Burka, Edward R. (1969)
The characteristics of degradation of reticulocyte ribonucleic acid (RNA) and ribosomes were studied in a whole erythroid cell lysate system. The process followed Michaelis-Menten kinetics, and indicated that RNA degradation in the erythroid cell is mediated by an enzyme previously isolated from reticulocyte hemolysates. Erythroid cell RNase activity had a temperature optimum of 50°C, a pH optimum of 7.0, was not energy dependent, was heat labile at physiologic pH, and was inhibited by Mg(++), Ca(++), and exposure to bentonite and deoxycholate. Free sulfhydryl groups were not essential for RNase activity. Of the substrates occurring naturally within the erythroid cell, isolated ribosomal RNA was most susceptible to the action of the enzyme, intact ribosomes least susceptible, and transfer RNA intermediate between them. Natural substrates were degraded completely to nucleotides in cell lysates. Competitive inhibition studies indicate that one enzyme system is capable of degrading both RNA and ribosomes, although the existence of more than one enzyme has not been excluded. Erythroid cell lysates quickly broke down polyribosomes into single ribosomes. The more rapid degradation of ribosomes, as compared with transfer RNA, which occurs in vivo, as opposed to findings in vitro, suggests that there is a special intracellular mechanism responsible for ribosome degradation in the maturing erythroid cell.